2020
DOI: 10.3390/v12060641
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus in West Africa: A Seroepidemiological Study between 2007 and 2012

Abstract: According to the World Health Organization, the entire African continent is at risk of a Zika outbreak. To increase data availability on the epidemiology of Zika virus circulation in Africa, we evaluated the immunity to Zika virus in a selected cohort of subjects from West Africa between 2007 and 2012. Human serum samples were collected in 2007 and in 2011/2012 from a cohort of 2–29-year-old subjects from Mali, Senegal, and The Gambia. A sample that tested positive by Zika virus IgG ELISA and by Zika virus mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In addition, ZIKV was first isolated from a febrile rhesus macaque in the Zika Forest near Entebbe, Uganda in 1947 (61,62). Since that time, serologic and molecular (RNA or virus isolation) evidence of continued circulation in Africa has been intermittently reported in humans, animals, and mosquitoes (63)(64)(65)(66)(67). Prior to a report from Guinea-Bissau from 2016, during which an outbreak and subsequent identification of infant microcephaly cases was attributed to an African lineage virus, there were no reports of ZIKV impacting pregnancies and infant development in Africa (63,68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ZIKV was first isolated from a febrile rhesus macaque in the Zika Forest near Entebbe, Uganda in 1947 (61,62). Since that time, serologic and molecular (RNA or virus isolation) evidence of continued circulation in Africa has been intermittently reported in humans, animals, and mosquitoes (63)(64)(65)(66)(67). Prior to a report from Guinea-Bissau from 2016, during which an outbreak and subsequent identification of infant microcephaly cases was attributed to an African lineage virus, there were no reports of ZIKV impacting pregnancies and infant development in Africa (63,68).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to a report from Guinea-Bissau from 2016, during which an outbreak and subsequent identification of infant microcephaly cases was attributed to an African lineage virus, there were no reports of ZIKV impacting pregnancies and infant development in Africa (63,68). This has led to a number of hypotheses as to why, which includes, but is not limited to the following: widespread immunity in populations of childbearing age due to infection earlier in life; masking of ZIKV-associated adverse outcomes due to a high number of other, co-circulating pathogens in many populations, such as malaria; or embryonic loss during very early pregnancy simply unrecognized due to unknown status or inconsistent access to prenatal care (63,64,69). The data generated in this work supports the latter hypothesis of early loss.…”
Section: Discussionmentioning
confidence: 99%
“…The low ZIKV seroprevalence three years after infection is in line with previous studies, in which it was shown that nAbs and NS1 antibodies against ZIKV decline rapidly, and indicate that ZIKV serology in flavivirus endemic populations is very challenging several years after the initial infection [ 11 , 12 ]. This could possibly in part explain why the reported ZIKV seroprevalence in regions in Africa and Asia, where ZIKV has already been circulating for many years, is low [ 21 , 22 , 23 ]. One possible solution to increase the sensitivity of ZIKV serological assays in populations that did not recently suffer from a ZIKV outbreak is to set a lower cut-off for a positive test result.…”
Section: Discussionmentioning
confidence: 99%
“…From 574 samples collected in 2013 in Kenya, five had confirmed positive IgM for ZIKV [24]. A seroprevalence study conducted between 2007 and 2012 in Senegal, Mali and Gambia, estimated a seroprevalence around 20-22% [25]. Altogether, these data confirm that ZIKV has been circulating for a long time in Africa, but for unknown reasons, has never been responsible for any large outbreak in this continent.…”
Section: Epidemiologymentioning
confidence: 75%